Mathematics
Alisonberg777
32

What is the solution to and please show step by step -6(3-k) = 6(1+3k)

+3
(2) Answers
Nancey591

-6(3) + -6(-k) = 6(1) + 6(3k) -18+6k=6+18k       -6k       -6k -18=6+12k   -6  -6 -24=12k  divide each side by 12 -2=k

Earlie318

you would divide eat side by 6 which would give you -3+k equals 1+3k. next you would subtract the 1 to the other side and subtract the k to the other side which would give you -4 equals 2k. Then you would divide both sides by 2 which would give you your answer of k equals -2

Add answer